IMPLEMENTASI TOTAL QUALITY MANAGEMENT (TQM) DI INSTITUT PTIQ JAKARTA - Ahmad Zain Sarnoto; Riwayati Wahyuningsih (Lembaga Penelitian dan Studi kebijakan MADANI Instutute, 2022)
Research on the implementation of Total Quality Management (TQM) was conducted at PTIQ Institute Jakarta. Research is more focused on the implementation of total quality management in the Graduate Program of PTIQ Jakarta Institute. This research uses a descriptive qualitative approach that is a study that intends to understand the phenomenon of what is experienced by the research subject. Data is obtained through research on documents and interviews with stakeholders. The results of this study are: First, the application of Total Quality Management (TQM) at PTIQ Jakarta Institute has been prepared based on the rector's decision. Completeness of the document has been owned although still not detailed to the lowest level. Second, the implementation is realized by giving duties to lecturers as the embodiment of the Rector's decision. However, the number of task implementers in the field is still not balanced with the number of tasks charged, so that there are some tasks that have not been completed Third, Total Quality Management (TQM) for Private Islamic Religious Colleges (PTKIS), at PTIQ Institute has been working on digitalization models to facilitate and streamline work. Support for creating apps has been provided, although it is still in a simple stage. Fourth, the model of digitalization of devices to manage quality assurance systems and strengthen human resources becomes an important variable in maximizing the quality of quality management in Islamic Religious Colleges